The understanding of media law and its impact towards Malaysia political practice / Amira Mohd Azamli ... [et al.] - Mohd Azamli, Amira; Hassan, Mohd Suffiean; Sah Allam, Siti Nurshahidah; Bakar, Mohd Hilmi (Faculty of Communication & Media Studies, 2022)
The overall purpose of the study is to find out the understanding of media law and its impact towards Malaysia political practice. Media has been important to the people especially now with the new media emerge with the use of internet in the Industrial Revolution 4.0. However, despite the growth of this media, there also been a lot of effect happened from the media law that had been created by the previous ruler and also to find out its influence on the political practice. This is where to investigate and find out the understanding and known about media law in Malaysia and how its gives impact toward political practice. There has been as many as 11 journals were chosen wisely after going through some process corresponded to the criteria.